2018
DOI: 10.3390/hydrology5030042
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic Characteristics of Streamflow in the Southeast Atlantic and Gulf Coast Hydrologic Region during 1939–2016 and Conceptual Map of Potential Impacts

Abstract: Streamflow is one the most important variables controlling and maintaining aquatic ecosystem integrity, diversity, and sustainability. This study identified and quantified changes in 34 hydrologic characteristics and parameters at 30 long term discharge stations in the Southeast Atlantic and Gulf Coast Hydrologic Region (Region 3) using Indicators of Hydrologic Alteration (IHA) variables. The southeastern United States (SEUS) is a biodiversity hotspot, and the region has experienced a number of rapid land use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Urbanization, increased agricultural use and forest management are the major land use change in the SRB (Zurqani et al 2018). However, a few other studies were found that focused on larger regions (e.g., Southeastern U.S., Georgia‐North Carolina‐South Carolina) encompassing SRB (Anandhi and Bentley 2018; Anandhi et al 2018a). For example, it was observed that Southeastern U.S. region is particularly vulnerable to a number of climate‐driven events and has been affected by more than billion‐dollar disasters than any other region in the country (Anandhi and Bentley 2018).…”
Section: Results Of Meta‐analysis For Components Of Dpsir Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…Urbanization, increased agricultural use and forest management are the major land use change in the SRB (Zurqani et al 2018). However, a few other studies were found that focused on larger regions (e.g., Southeastern U.S., Georgia‐North Carolina‐South Carolina) encompassing SRB (Anandhi and Bentley 2018; Anandhi et al 2018a). For example, it was observed that Southeastern U.S. region is particularly vulnerable to a number of climate‐driven events and has been affected by more than billion‐dollar disasters than any other region in the country (Anandhi and Bentley 2018).…”
Section: Results Of Meta‐analysis For Components Of Dpsir Frameworkmentioning
confidence: 99%
“…Similarly, many basins throughout Georgia, North Carolina, and South Carolina have been undergoing considerable urbanization trends over decades, which is expected to continue (Wrona et al 2007). The Southeastern U.S. has experienced rapid land use/land cover change during the 19th and early 20th Centuries due to conversion of forests to agriculture (lowest around 1920s), then conversion of agriculture back to forest after the Great Depression (during 1930s), followed by forest fragmentation during the economic boom (1980s to 2000s) and, recently, the conversion of agricultural land use to urban/suburban development (Anandhi et al 2018a).…”
Section: Results Of Meta‐analysis For Components Of Dpsir Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…This case study is based on three studies in several states in the southeastern U.S. (Anandhi and Bentley, 2018;Anandhi et al, 2018aAnandhi et al, , 2018b. Together, these studies used a broad definition of the land-resource system (multiple elements including land use, water resources, other natural resources, climate, biological systems) and stressors (multiple elements including precipitation and temperature change, land-use change, changes in other natural resources).…”
Section: Case Study 5: Broader Definition Of a Land Resource System Amentioning
confidence: 99%